A study on surface slant encoding in V1 - Siddiqui, M Sultan M.; Bhaumik, Basabi (Frontiers in Systems Neuroscience, 2013)
Inter-ocular differences in spatial frequency occur during binocular viewing of a surface slanted in depth. Cortical cells with inter-ocular differences in preferred spatial frequency (dif-frequency cells) are expected to detect surfaces slanted in depth or vertical surface slant. Using our reaction-diffusion model, we obtain receptive fields and responses of simple cells in layer IV in cat V1. The dif-frequency cells in the model cortex have tilt in binocular receptive field but we show that tilt by itself does not indicate slant selectivity. We studied cell responses to binocular combination of spatial frequencies (SFs) by varying the SF ratio of the input gratings to the left and right eye in the range of 0.35 to 3. This range of SF ratio corresponds to surface slant variation of −85° to 85°. The mean binocular tuning hwhh (half width at half height) is 41°. Except for a small number (2.5%) of cells, most dif-frequency cells respond almost equally well for fronto-parallel surfaces. In the literature cells with inter-ocular difference in preferred orientation (IDPO) were expected to encode horizontal surface slant. In the model cat V1 mean hwhh in binocular orientation tuning curve for cells with IDPO is 39°. The wide binocular tuning width in dif-frequency cells and cells with IDPO imply that in cat V1 neither dif-frequency cells nor cells with IDPO detect surface slant.